Plant size of the alpine cushion Thylacospermum caespitosum affects soil amelioration at different elevations - Zhao, Ruiming; An, Lizhe (Plant ecology, 2021)
Cushion plants (as nurse species) can ameliorate soil conditions under their canopy in alpine environments. However, this amelioration (or the intensity of soil fertility islands) related with the size of plants is rarely studied. To assess size effects of Thylacospermum caespitosum on soil fertility islands, soil properties (pH; electric conductivity, EC; soil organic carbon, SOC; available nitrogen, AN; available phosphorus, AP; available potassium, AK) and microbial biomass (soil microbial biomass carbon, SMBC; soil microbial biomass nitrogen, SMBN) were investigated at three different elevations in the Qilian Mountains. Plant size significantly influenced (P < 0.001) soil properties (pH, EC, SOC, AN, AP, AK) and microbial biomass (SMBC and SMBN) at all three elevations. A size-dependent fertile island effect occurred beneath T. caespitosum, where the relative interaction index (RII) of soil properties and SMBC was affected (P < 0.001) by plant size at the three elevations. Moreover, most parameters of soil nutrition and microbial biomass under T. caespitosum were reduced (P < 0.001) with increases in elevation, but the RII was increased (P < 0.05). In short, soil amelioration by T. caespitosum was clearly dependent on plant size at all elevations, and this effect on soil increased with elevation. Thus, the existence of size-dependent fertility islands together with elevation should be regarded as a central mechanism of the nurse effect of T. caespitosum in harsh alpine ecosystems, where many ecological processes rely on the nurse effect of cushion plants.